Institutio sui Generis: Searching for a Global Catholic University during the 1970s - Duque, Lemke (Religions, 2023)
This study provides a critical look at the Catholic search for a global university of the future during the 1970s. It focuses on proposals and arguments from the Canadian theologian and sociologist Hervé Carrier SJ (1921–2014), who was rector of the Pontificia Università Gregoriana between 1966 and 1978. To understand his idea of the university, three aspects are key: firstly, French and German sociologists’ postwar dialogue on modern secularization; secondly, Karl Jaspers’s (1883–1969) concept of the unconditional search for truth; and thirdly, the lifelong education paradigm as a tool for regaining a supposed authenticity of the individual, conceived as a prerequisite for society and politics. Analyzing these keys brings out a critical evaluation of the limits associated with the subjectivity consciousness development at Catholic higher education institutions.